线性振动马达 (2018)
本发明提供了种线性振动马达，包括外壳、振子以及固定在外壳上并且与振子平行设置的定子，其中，振子包括振动块；振动块包括至少个永磁铁，定子包括导磁块；导磁块受到与振子的振动方向相同和/或者相反的磁场力的作用；其中，当振子处于平衡状态时，磁场力的合力为零；当导磁块受到激发力的作用在振子的振动方向上与振子发生相对位移时，磁场力的合力方向与相对位移的方向相同，且，磁场力的合力大小与相对位移的大小成正比例关系。利用上述发明，通过导磁块与永磁铁之间的自驱动作用，在其自由振动状态下容易得到较大的振感，同时极大缩短系统工作的启动时间。 A linear vibration motor, comprising a housing, a vibrator and a stator fixed on the housing and arranged in parallel with the vibrator. The vibrator comprises a vibration block, the vibration block comprises at least one permanent magnet (7a, 7b, 7c), the stator comprises conductive blocks (3a, 3b), and the conductive blocks are subject to the effect of a magnetic field force which is the same as and/or opposite to the vibration direction of the vibrator. When the vibrator is in a balanced state, the resultant force of the magnetic field force is zero. When the conductive blocks are subject to the effect of an excitation force and undergo displacement relative to the vibrator on the vibration direction of the vibrator, the resultant force direction of